Lethal now or lethal later: The natural history of Grade 4 blunt cerebrovascular injury. Issue 6 (June 2015) - Lauerman, Margaret H.; Feeney, Timothy; Sliker, Clint W.; Saksobhavivat, Nitima; Bruns, Brandon R.; Laser, Adriana; Tesoriero, Ronald; Brenner, Megan; Scalea, Thomas M.; Stein, Deborah M.
Abstract : BACKGROUND: Grade 4 blunt cerebrovascular injury (BCVI4) has a known, significant rate of stroke. However, little is known about the natural history of BCVI4 and the pathophysiology of subsequent stroke formation. METHODS: A 4-year review of patients with BCVI4 at the R Adams Cowley Shock Trauma Center was performed. Rates of BCVI4-related stroke, stroke-related mortality, and overall mortality were calculated. The relationship of change in vessel characteristics and BCVI4-related stroke was examined, as was the mechanism of stroke formation. RESULTS: There were 82 BCVI4s identified, with 13 carotid artery (ICA) and 69 vertebral artery BCVI4s. BCVI4-related stroke rate was 2.9% in vertebral artery BCVI4 and 70% in ICA BCVI4 patients surviving to reimaging. Stroke mechanisms included embolic strokes, thrombotic strokes, and combined embolic and thrombotic strokes. Peristroke vessel recanalization and an embolic stroke mechanism were seen in 100% of ICA BCVI4-related strokes developing after admission. BCVI4-related stroke occurred within 10 hours of hospital admission in 67% of the patients with strokes. Contraindications to anticoagulation were present in most patients with BCVI4-related stroke developing after admission. CONCLUSION: Multiple etiologies of stroke formation exist in BCVI4. Early risk-benefit analysis for initiation of anticoagulation or antiplatelet agents should be performed in all patients with BCVI4, and the use of endovascular vessel occlusion should be considered in those with true contraindications to anticoagulation. However, more aggressive medical therapy may be needed to lessen BCVI4-related stroke development. LEVEL OF EVIDENCE: Prognostic study, level IV; therapeutic study, level V.